2019
DOI: 10.1111/cea.13506
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary angioedema: Looking for bradykinin production and triggers of vascular permeability

Abstract: Since the Osler's identification of the inherited nature of hereditary angioedema, a huge array of information was collected on pathogenetic mechanisms of the disease. Over the last years, information grew fast, and mutations in different genes, in addition to C1‐inhibitor, were found to be causative. All types are inherited as autosomal‐dominant traits with incomplete penetrance and little or no genotype‐phenotype correlation. As a result, the clinical expression is characterized by a large heterogeneity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
0
9
0
5
Order By: Relevance
“…Predictive functional profiling of microbial communities was consistent with the above findings. Luminal expansion of Proteobacteria was also observed in humans with irritable bowel syndrome [43][44] , inflammatory bowel disease [45][46][47] , necrotizing enterocolitis 9 and colorectal cancer [48][49] , and may represent a marker of the destruction of intestinal epithelial barriers and induction of gut inflammation. Decreased Proteobacteria abundance was observed among patients with HAE taking danazol or tranexamic acid, and thus may represent a useful marker for therapeutic evaluation in clinical practice.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Predictive functional profiling of microbial communities was consistent with the above findings. Luminal expansion of Proteobacteria was also observed in humans with irritable bowel syndrome [43][44] , inflammatory bowel disease [45][46][47] , necrotizing enterocolitis 9 and colorectal cancer [48][49] , and may represent a marker of the destruction of intestinal epithelial barriers and induction of gut inflammation. Decreased Proteobacteria abundance was observed among patients with HAE taking danazol or tranexamic acid, and thus may represent a useful marker for therapeutic evaluation in clinical practice.…”
Section: Discussionmentioning
confidence: 93%
“…Ample evidence has shown that HAE has variable clinical features, with significant interindividual diversity in triggers, prodromal signs, age at first onset, attack frequency, attack severity, and edema locations 24 . Numerous studies have investigated the mechanisms underlying phenotypic diversity and the triggers for vascular leakage 9,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical variability and incomplete penetrance are still challenging characteristics for the diagnosis of the different HAE variant forms recognized to date. Although a major influence of environmental factors is evident (as exemplified by estrogen exposure in the case of HAE-FXII patients), part of the variability can also be ascribed to disease-modifying genes ( Margaglione et al, 2019 ). Most of the HAE disease-modifiers identified are related with changes in the plasma activity of bradykinin catabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%